Istishna’ Contract Application In The 57 Plisket Convection Business - Nafisah, Nihayatun (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2022)
Istishna' financing is a sales contract where the price of the goods is paid in advance, but can be paid in installments according to agreed terms. The problem of this research is how to apply the istishna contract to the 57 plisket convection business and the provisions of muamalah fiqh. The type of research method used is literature review. The source of the literature review journal comes from the Al-Tsaman journal from the IAIN Jember. The aim is to explain the application of Istishna 'contracts in the 57 plisket convection business, and to find out the provisions of muamalah fiqh that are in accordance with the Islamic economy